Articulating Organisational Culture - Cain, Justin (My University, 2011)
Scholarly literature suggests that organisational culture is a significant force within an organisation. The ability to interpret an organisation’s culture would therefore be useful. This report develops and demonstrates a research methodology to investigate the culture of the organisation. The methodology is based on the ontological assumption of the corporation being a ‘Work’, the kind of entity that sets up a ‘World’ for people as developed from the hermeneutic phenomenological tradition. A ‘World’ in this sense is the collection of interpretations within which human beings make sense of their existence. Building on existing approaches that are based on an understanding of organisational cultures similar to a ‘World’ in the hermeneutic phenomenological sense, the report develops a qualitative methodology that consists of a series of questions posed to members of the organisation to articulate the fundamental assumptions and interpretations of the culture of a specific company. The report proceeds to show the insights obtained in applying this type of research to understanding the ‘World’ or culture of a South African utility company. The key findings of the report established that the proposed method was able to give a rich in-depth insight into the ‘World’ and culture of the company in a way that proves to be a useful and valuable method to interpret organisational culture which can be used to inform management decisions.
MBA - WBS
Keywords: Organisational culture